Perubahan Peran dan Transformasi Fungsi Sumber Daya Manusia dalam Mewujudkan Good Corporate Governance dan Corporate Social Responsibility - Wahyu Mujarudin (Jurnal Manajemen Maranatha, 2006)
The raising and tightening global competition lately forces company to change its strategy due to establish and increase the company. It aimed to win the competition through competitive advantage which is built by the company. To gain that goal, a company needs to enforce basic company’ workship which is should be better in every aspects (leadership, individual role, organization structure and design, bussiness strategy, technology, and market consideration). To achieve those points, the exact roles of each component in the company is highly needed, especially the role of human resource which is the most valuable asset of the company. The role which is played by the human resource component is a role that in the connection to the business isues and strategies rather than traditional functions. Thus, in order to achieve the new role from the human resourcer, a company needs repositioning and transformating the human resource role and functions. The changing of this role and function of human resource hopefuly will be able to create a company that has responsibility, fairness, transparency, independency and accountability, so the Good Corporate Governance and Corporate Social Responsibility could be realized.